(untitled) (Journal of Academic Research, 2024)
Background: The optimal drug for reducing emergence agitation (EA) after sevoflurane anesthesia remains unclear, with both propofol and fentanyl as potential options. Aim: This study aimed to compare the effects of fentanyl and propofol on the incidence and severity of postoperative agitation and excitement following sevoflurane anesthesia. Methods: Sixty-six children who underwent sevoflurane anesthesia were prospectively assigned to three groups. Group P received propofol 1 mg/kg, Group F received fentanyl 1 μg/kg, and Group S received saline. EA was assessed using the Pediatric Anesthesia Emergence Delirium (PAED) scale, alongside recovery time and the occurrence of nausea and vomiting. Results: Group P and Group F had mean PAED scores of 5.05 and 5.2, respectively (p=0.715), significantly lower than Group S (14, p<0.001). Group F had a significantly higher frequency of nausea and vomiting compared to Group P (p<0.001), while differences between Groups P and S were not clinically significant. Group P had a shorter stay in the post-anesthesia care unit (PACU) than Group F (p=0.06), though this difference was not clinically significant. However, Group F had a significantly longer PACU stay than Group S (p=0.01). Conclusion: Both propofol and fentanyl reduced the incidence of EA after sevoflurane anesthesia, but propofol was associated with a lower rate of nausea and vomiting, making it the preferable option.